Private Activity in Infrastructure in the Middle East and North Africa Remained at low Levels in 2010 - World Bank (World Bank, Washington, DC, 2012)
In 2010, three infrastructure projects with private participation reached financial or contractual closure in three low- and middle-income countries, involving investment commitments of US$1.1 billion. Infrastructure projects implemented in the 1990-2009 period attracted new investment of US$5.8 billion, bringing total investment commitments (hereafter, investment) to infrastructure in the region to US$6.9 billion in 2010. This level of investment is similar to the one reported in the region in 2009 (US$6.8 billion). However, private activity by number of projects is one third of the one reported in 2009 during the previous year (nine new projects in 2009).